Población anidante e impacto en la pesca artesanal del cormorán neotropical Phalacrocorax brasilianus Suliformes:Phalacrocoracidae), en el sitio Ramsar Cerrón Grande, El Salvador. - Herrera, N. (Universidad de El Salvador, 2016)
The neotropical cormorant (Phalacrocorax brasilianus) is a species of waterfowl abundant in the wetlands of El Salvador. Fish predation on aquatic ecosystems is generating a conflict with fishermen that associating declining fishing with predatory behavior of this bird. From April 2010 to February 2011, an investigation was conducted aimed at knowing the state of the population of P. brasilianus in the Ramsar wetland Cerron Grande, El Salvador. The study was conducted through counting and collecting of birds, to analyze the stomachic contents. The maximum recorded was 28.063 individuals and 3,000 breeding pairs. 266 birds were collected, on 207 it found fish in their stomachs, whose individual weight ranged from 2-307 g ± 52 g. A total of 1,078 fish specimens was found, from ten species, four of them obtained the highest values of abundance: bagre (Cathorops steindachneri) with 29%, followed by guapote (Parachromis managuensis) with 25%, tilapia (Oreochromis niloticus) with 22% and plateada (Astyanax aeneus, Roeboides bouchellei) with 31%.